ANALISIS PERAMALAN RASIO PROFITABILITAS BANK TABUNGAN NEGARA SYARIAH MENGGUNAKAN METODE ANALISIS TREND KUADRATIK - M ZAKI MUBARAK LUBIS (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2022)
The primary factor in the investment that investors will issue is profitability. Although a company's prospects can be determined, it is required to predict the production that will be generated in order to identify potential future markets. By utilizing the Return on Assets (ROA) and Return on Equity (ROE) ratios, this study aims to examine forecasting the profitability ratios at the Islamic State Savings Bank (BTN). The data ranges from 2016 to 2021. Quadratic trend analysis is used to process the data. The forecasting of ROA and ROE using the quadratic trend approach may be summarized based on the findings of the study that has been done as follows: namely the results of forecasting ROA BTN Syariah of 0.9514 in 2022, 1.312 in 2023 and 1.7994 in 2024. Meanwhile ROE of BTN Syariah is 17.088 in 2022, 23,988 in 2023 and 32,768 in 2024.